The Effect of Using Lumi Education on Improving Students' Motivation in Teaching Arabic Language and Learning Outcomes - Sintya Rahmadewi; Miftahul Huda; Faisal Mahmoud Adam Ibrahim (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Arabic language learning in secondary schools still faces challenges related to low student motivation and learning outcomes due to the use of traditional teaching methods. This study aims to determine the effect of using Lumi Education on students’ motivation and Arabic language learning outcomes at a public senior high school in Batu. This study employed a quasi-experimental design with a pretest–posttest model involving experimental and control groups, consisting of 60 seventh-grade students. Data were collected through observation, motivation questionnaires, and achievement tests covering vocabulary, grammar, and phonetics. The data were analyzed using SPSS 26 through normality tests, homogeneity tests, and t-tests. The results showed that the use of Lumi Education significantly increased students’ learning motivation (80.13%) compared to the control group (62.6%) and improved learning outcomes, with a posttest mean score of 79.2 in the experimental group and 72.13 in the control group. This study contributes to the development of effective and innovative Arabic language learning based on digital media.